ANALISIS PENGGUNAAN DEIKSIS DALAM INTERAKSI MAHASISWA UNIVERSITAS DHARMAS INDONESIA - Dayu Astuti; Fitri Samila; Pitri Wati; Toni Edison (Dharmas Education Journal (DE_Journal), 2024)
This study aims to analyze the use of deictics in student interactions at the campus of Dharmas Indonesia University (UNDHARI) using a pragmatic approach. Deictics are linguistic elements whose meaning depends on the speaker’s context, as well as the time and place of the utterance. The study employs a qualitative descriptive method with data collection techniques including observation, recording, note-taking, and unstructured interviews. Data analysis involves identifying types of deictics and analyzing their usage. The results indicate that Undhari students use five types of deictics: personal, temporal, spatial, discourse, and social deictics. The use of these types of deictics reflects social relations, communicative situations, and the level of familiarity among speakers. Furthermore, the understanding of deictic meaning is significantly influenced by context. This study is expected to contribute to pragmatic studies and enhance awareness of appropriate language use in communication.